PENGARUH GOOD CORPORATE GOVERNANCE, AUDITOR EKSTERNAL, FIRM SIZE, LEVERAGE TERHADAP TAX AVOIDANCE (Study Empiris Pada Perusahaan Terdaftar Di Forum Corporate Governance Indonesia (FCGI) Tahun 2011-2013) (Students' Journal of Accounting and Banking, 2015)
This study aims to analyze the influence of good corporate governance, external auditors, firm size and leverage against tax avoidance.In this study popuation are used companies registered in Forum Corporate Governance Indonesia (FCGI) of the years 2011 to 2013, enter the rating application of corporate governance conducted by The Indonesia Institute for Corporate Governance (IICG) of the years 2011 to 2013 in the form of score ranking by CGPI (Corporate Governance Perception Index) and the Indonesia Stock Exchange (IDX), published SWA magazine of the years 2011 to 2013. The sampling technique using purposive sampling. Mechanical testing data is to use a multipe linear regression analysis. The analysis showed that the variables good corporate governance and firm size in 2011, 2012, and 2013 had no effect on tax avoidance. External auditors in 2011 a positive effect on tax avoidance, in 2012 external auditors has no effect on tax avoidance,in 2013 external auditors negative effect on tax avoidance. Leverage in 2011 and 2013 had no effect on tax avoidance, while in 2012 leverage negative affect on tax avoidance.Keywords: Good Corporate Governance, External Auditors, Firm Size, Leverage, and Tax Avoidance